The Effect of the Thioether-Bridged, Stabilized Angiotensin-(1–7) Analogue Cyclic Ang-(1–7) on Cardiac Remodeling and Endothelial Function in Rats with Myocardial Infarction - Matej Durik; Richard van Veghel; Anneke Kuipers; Rick Rink; Marijke Haas Jimoh Akanbi; Gert Moll; A. H. Jan Danser; Anton J. M. Roks (International Journal of Hypertension)
Modulation of renin-angiotensin system (RAS) by angiotensin-(1–7) (Ang-(1–7)) is an attractive approach to combat the detrimental consequences of myocardial infarction (MI). However Ang-(1–7) has limited clinical potential due to its unfavorable pharmacokinetic profile. We investigated effects of a stabilized, thioether-bridged analogue of Ang-(1–7) called cyclic Ang-(1–7) in rat model of myocardial infarction. Rats underwent coronary ligation or sham surgery. Two weeks thereafter infusion with 0.24 or 2.4 μg/kg/h cAng-(1–7) or saline was started for 8 weeks. Thereafter, cardiac morphometric and hemodynamic variables as wells as aortic endothelial function were measured. The average infarct size was 13.8% and was not changed by cAng-(1–7) treatment. MI increased heart weight and myocyte size, which was restored by cAng-(1–7) to sham levels. In addition, cAng-(1–7) lowered left ventricular end-diastolic pressure and improved endothelial function. The results suggest that cAng-(1–7) is a promising new agent in treatment of myocardial infarction and warrant further research.